Svetovalčev notranji dialog kot pomoč ali ovira pri vodenju svetovalnega pogovora? - Rakovec, Primož (Socialno delo, 2023)
The outcome of the counselling process is also influenced by so-called common factors. We classify them into the client, environment, relationship, method, and counsellor factors. The counsellor’s inner experience is also included among the counsellor’s factors. Internal dialogue plays an important role in the processes of inner experience. Dialogue can be positive and as such help the counsellor in leading the counselling conversation, or negative, which means that the counsellor is hindered in communicating with the user. Internal dialogue serves as an interpreter and evaluator of external and internal events, followed by changes in emotions and behaviour. The research showed that counsellors are aware of the importance of the impact of internal dialogue. Self-instructions play a very important role during the counselling conversation, as the counsellor does not face too many unhealthy negative emotions, which allows him/her to perform functional behaviors within the counselling relationship that helps the user to achieve the counselling goal.
Keywords: behaviour; counselling; čustva; efficiency; emotions; samoinštrukcije; self-instructions; svetovanje; učinkovitost; vedenje